Pediatric cannabis poisonings in France: more and more frequent and severe. (3rd April 2021) - Chartier, Céline; Penouil, Françoise; Blanc-Brisset, Ingrid; Pion, Charlotte; Descatha, Alexis; Deguigne, Marie
Abstract: Context: Accidental pediatric cannabis poisonings are an incidental effect of cannabis use. The average THC content of cannabis resin and the number of consumers are rising sharply in the USA and in most European countries. The objective is to study the evolution of prevalence and severity of pediatric exposures to cannabis in France. Method: This is a retrospective observational study of cases detected by French poison centers between January 1 st 2010 and December 31 st 2017 of cannabis exposure by ingestion in children aged ten or younger. The clinical severity was assessed using the Poisoning Severity Score (PSS). The criteria used for assessing the overall severity were as follows: PSS ≥ 2, admission to pediatric intensive care, coma and respiratory depression (univariate and multivariate logistic regression). Results: A total of 965 cases of poisoning were covered. The annual average number of cases was 93 between 2010 and 2014 and 167 between 2015 and 2017. The median age was 15 months (range, 6 months–10 years) and the sex ratio was 1:1. The form of cannabis ingested was mainly resin (75%). During the period covered by the study, 26.1% of children ( n = 252) presented with a PSS ≥ 2, 4.5% ( n = 43) coma, 4.6% ( n = 44) with respiratory depression and 11.7% ( n = 113) were admitted into pediatric intensive care (out of 819 hospitalizations). No fatal cases were reported. In comparison to the 2010–2014 period, the length of hospital stays was significantly higher ( p < 0.0001) and the comas were significantly deeper (lower score on the Glasgow coma scale, p < 0.005) in 2015–2017. Following adjustments made for the sex, age and weight of the children, the data show that the severity of the poisonings was significantly greater in 2015–2017 in terms of PSS score, the number of comas and monitoring in intensive care ( p < 0.001). Conclusion: The data indicates a significant increase in the number of cases of pediatric exposure to cannabis and a rise in the seriousness of poisonings between 2010 and 2017.